KARAKTERISTIK KONSUMEN PRODUK ROTI CELLA BAKERY DAN HOLLAND BAKERY DI MANADO - Antonius Brian Regar; Jenny . Baroleh; Leonardus R. Rengkung (Sam Ratulangi University, 2015)
The aim of this study was to describe factors that distinguish consumers in selecting Bread Product Cella Bakery Holland Bakery. This study uses primary data were taken from interviews with respondents (Consumer Bread Product Cella Bakery and Holland Bakery) which incidentally encountered were making purchases at Cella Bakery and Holland Bakery by using a list of questions (questionnaire) were analyzed descriptively presented in tabular form. This study can provide information for producers to know and understand the characteristics of the consumers in order to increase sales. The results showed that the Ethnographic Characteristics (Ethnic) Cella Bakery and Holland Bakery Consumer in general is Minahasa suspected in general people of Manado come from ethnic Minahasa, Geographic Characteristics where the distance residential customers with Cella Bakery and Holland Bakery does not affect consumers in obtaining and consume Bread Product Cella Bakery and Holland Bakery, Demographic Characteristics of Cella Bakery and Holland Bakery Consumer generally women, were between the ages of 18-34 years, middle-income, number of family members / dependents between 3-4 people, with education past high school, and Psychographic Characteristics generally Cella Bakery Consumers frequently consume bread fried namely Panada by reason of having good taste, before eating bread in the shop and in the year> 2002 began to consume bread in Cella Bakery and Holland Bakery Consumer frequently consume bread baked are mocha brown bread fill the grounds have good taste, before eating bread at the mall and in the year> 2002 began to consume bread in Holland Bakery.